IMPROVING THE BUREAUCRATIC PRESTIGE THROUGH CORRUPTION-FREE PUBLIC SERVICE SYSTEM - DAILIATI, SURYA (Human Sustainability Procedia, 2018)
The objective of this research is to reveal and analyze how improving the bureaucratic prestige through corruption-freepublic service system.The method used in this research is descriptive qualitative, which aims to improve the bureaucratic through corruption-free public service system. The data collection used, as common in qualitative research are observation, interviews and documentation. The collected data were analyzed with interactive model of Miles and Huberman. The research result indicated that to improve the bureaucratic prestige through corruption-free public service system, the government policies, programs and activities in the future leadership era are directed and positioned correctly as a strategy of implementing bureaucratic reform in eradicating corruption to create a good public service system. Bureaucratic reforms really become ideologies that are internalized or well transformed in the form of government policies or programs. The drive to set the speed in the public services system and electronic public services can be used as the initial momentum to improve the bureaucracy prestige especially in the public services